ANALYSIS OF IMPLEMENTATION OF PKN LEARNING IN SOCIALIZED LIFE IN CLASS V STUDENTS OF SDN PAYA PEUNAGA - Desi Amelia (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the implementation of PKN learning in socializing life in grade V SDN Paya Peunaga. The method used in this research is descriptive method. The samples that were observed were all students of grade V SD Negeri Paya Peunaga, totaling 20 people. The data collection methods used were observation, written test, questionnaire and documentation. The parameters used are student behavioral activities, which include a reflection, the values of Civics learning that are obtained and implemented in social life in class V SD Negeri Paya Peunaga both inside and outside the classroom have been carried out well, because learning is able to provide Civics values directly in the student's own environment so that these students can interact with each other in everyday life. Based on the results of the questionnaire on the questions in the questionnaire which shows the percentage of students who answered agree and strongly agree. The results of observations of teachers in the teaching and learning process at SD Negeri Paya Peunaga, it is known that the average observation result is 3.4%. Because almost all aspects of the observed teachers score very well and well and it can be stated that in the teaching and learning process, the teacher has implemented it well and optimally. And in Civics learning, students get a good predicate and assessment where there are 18 students who complete out of 20 students or 90,.